2015
DOI: 10.14202/vetworld.2015.197-202
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of carbohydrate and protein content of some forage feeds of ruminants for nutritive evaluation

Abstract: Aim:To evaluate some forage feeds of ruminants in terms of their carbohydrate (CHO) and protein fractions using Cornell Net Carbohydrate and Protein System (CNCPS).Materials and Methods:Eleven ruminant feeds (six green fodders - maize, oat, sorghum, bajra, cowpea, berseem and five range herbages - para grass, guinea grass, hedge lucerne, setaria grass and hybrid napier) were selected for this study. Each feed was chemically analyzed for proximate principles (dry matter, crude protein [CP], ether extract, organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 9 publications
(10 reference statements)
1
19
0
3
Order By: Relevance
“…In proximate analysis, VS is more important because only VS fractions are digestible and found in the rage of 61.23 to 70.33% with the order of SB>WS>MS>CC>AS and these results supported by previous study. These results of proximate and ultimate analysis are in line and supported by literature, 16,17 however, few variation was observed in literature might be because of biomass growth parameters variations like growing and environmental (soil, plant maturity stage and seasonal difference) conditions as reported variation parameters in literature. 18 These ultimate data are used for balancing C/N ratio and help in predicting BMP CHNO .…”
Section: Resultssupporting
confidence: 89%
“…In proximate analysis, VS is more important because only VS fractions are digestible and found in the rage of 61.23 to 70.33% with the order of SB>WS>MS>CC>AS and these results supported by previous study. These results of proximate and ultimate analysis are in line and supported by literature, 16,17 however, few variation was observed in literature might be because of biomass growth parameters variations like growing and environmental (soil, plant maturity stage and seasonal difference) conditions as reported variation parameters in literature. 18 These ultimate data are used for balancing C/N ratio and help in predicting BMP CHNO .…”
Section: Resultssupporting
confidence: 89%
“…Among the studies included in the present analysis, none reported details on protein fractions, but previous studies reported higher fibre‐bound N in cowpea and alfalfa forage compared with maize and sorghum forage (e.g. Chrenková et al., ; Das, Kundu, Kumar, & Datt, ), although others found no differences between alfalfa and maize silages (Brito & Broderick, ). Besides the dissimilarities in protein fractions between forages, fibre‐bound N is known to increase in response to heating such as during ensiling (Weiss & Conrad, ).…”
Section: Discussionmentioning
confidence: 88%
“…Van Soest et al (1991) have introduced the analysis of plant cell wall by using neutral detergent and acid detergent solutions to generate neutral detergent fiber (NDF) and acid detergent fiber (ADF), respectively. The residual part of the analysis can be subsequently continued with nitrogen determination to produce a neutral detergent insoluble crude protein (NDICP) and an acid detergent insoluble crude protein (ADICP) (Licitra et al, 1996;Das et al, 2015). Apart from their native presences in plant cell wall, NDICP and ADICP contents are higher in the feed materials dried at high temperatures due to caramelization and browning reactions; the non-enzymatic browning or Maillard reaction causes the condensation of carbohydrate degradation products with protein to form dark-coloured and insoluble polymers (Pelletier et al, 2010;Khan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%